FENOMENA BULLYING PADA MIS DAN RESPON MAYARAKAT TANJUNG LENGGANG TERHADAP KAJIAN FIKIH MINGGUAN DALAM PRESPEKTIF MODERASI BERAGAMA - Zulkarnain, Zulkarnain; Umair, Muhammad; Haitami, Hafiza; Kinanti, Aprillia; Salsabila, Asti (UIN Sumatera Utara Medan, 2026)
Using a perspective of religious moderation, this study intends to investigate the phenomenon of bullying in Private Islamic Elementary Schools (MIS) and the Tanjung Lenggang community's response through socialization techniques and da'wah in weekly fiqh lessons. Students, educators, and the community are regularly exposed to fiqh teachings that prioritize the virtues of compassion, justice, and tolerance through the methods of socialization and da'wah. The study's findings demonstrate that this approach works well for fostering social cohesion and raising knowledge of bullying prevention. In conclusion, bullying in the educational setting can be lessened by da'wah and socialization based on Islamic moderation.